Dilema Branding Madrasah di Kawasan Pariwisata: Sinkronisasi Nilai Lokal Bali dan Identitas Religius - Saiful Bahri (Visionaria: Journal of Educational Innovation Management, 2025)
This study examines the branding dilemma of a madrasah located in a tourism area, using MA Cahaya Cendikia Bali as the primary case study. The research aims to analyze the forms of identity tension that emerge and the managerial strategies employed to reconcile local Balinese values with Islamic religious identity within a multicultural society. A qualitative descriptive approach was adopted, utilizing interviews, observations, and documentation as the main data sources. The findings indicate that the madrasah faces challenges in maintaining a religious image while simultaneously responding to the socio-cultural openness demanded by a tourism-driven environment. Management efforts such as integrating local values, strengthening social participation, and utilizing digital media have been undertaken; however, their implementation remains inconsistent and largely partial. This study contributes to the development of identity management concepts in Islamic educational institutions by proposing a more adaptive, collaborative, and context-sensitive model of religious–cultural branding aligned with the dynamics of Bali’s tourism context.